Web arte X Web design: conflitos e aproximações - Silva, Roseane Romão da (2010)
After the expansion and popularization of information technology and the Internet, there are projects that integrate computational aspects and aesthetic intentions. The difficult task of identifying them and categorize them as art and as web design is the subject of this research. The main purpose involves research and mapping of digital design. Then be presented criteria defining web art and web design. Are proposed, based on case studies a comparative analysis of projects web sites art sites and digital design. The theoretical research is based on various authors such as Lucia Santaella, Clement Mok, Claudia Giannetti, Vicente Gosciola, Diana Domingues, Fabio Oliveira Nunes, Gilbertto Prado and Lucia Leão